STUDENTS’ INTEREST IN LEARNING ENGLISH - Manurung, Friscka; Supardi, Iwan; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is conducted to reveal the students’ interest in learning English. Moreover, this research reports the level of interest of the students in learning English. The participants (n=77) were the third semester students of Indonesian Language Study Program Tanjungpura university. This study used Students’ Interest Questionnaire adapted from Yu (2010) as an inventary to explore the level of students’ interest in learning English. The method that was used in conducting this research was descriptive method. The result revealed that most of the participants had the high interest in learning English which is out of the 77 participants, there were 40 (52%) students are labeled as the high interest students. 29 (38%) of the students are labeled as very high interest students. The remain 8 (10%) students are labeled as a medium interest students. Among the eight aspects of the interest in learning English, Language Value was the most dominat aspect of the interest in learning English of the students with the percentage of 15%. The overall result suggests that students of Indonesian Language Study Program Tanjungpura University have significant tendency in learning English. Keyword : Students’ Interest, Learning English